Occurrence, pathogroup distribution and virulence genotypes of Escherichia coli from fresh seafood. (March 2022) - Prakasan, Sreepriya; Lekshmi, Manjusha; Ammini, Parvathi; Balange, Amjad K.; Nayak, Binaya Bhusan; Kumar, Sanath H.
Abstract: Seafood contamination with pathogenic Escherichia coli is a significant public health threat in developing countries. In this study, the prevalence of different pathogroups of E. coli was investigated in fresh seafood. A total of 78 samples comprising of finfish (41) and shellfish (37) were analyzed using multiple selective-enrichment-isolation protocols. From all samples, 639 E. coli were isolated and tested for the presence of pathogroup-specific virulence-associated genes by polymerase chain reaction (PCR). Based on the distribution of virulence genes, 118 isolates belonged to enterohemorrhagic E. coli (EHEC) group, 25 to enteropathogenic E. coli (EPEC), 20 to enterotoxigenic E. coli (ETEC), 16 to enteroaggregative E. coli (EAEC) and 1 to enteroinvasive E. coli (EIEC). Fifty-five samples of seafood, 29 finfish and 26 shellfish, were found contaminated with pathogenic E. coli . Among different enrichment broth-selective agar combinations used for the recovery of pathogenic E. coli from seafood, enrichment in Tryptone Phosphate (TP) broth followed by isolation on sorbitol MacConkey (SMAC) agar performed superior to others. The study highlights the importance of using selective isolation and genotyping protocols to identify human pathogenic E. coli in seafood in regions with extensive anthropogenic contamination. Highlights: Diverse pathogroups of Escherichia coli in seafood represent consumer health risk. The EHEC group was the predominant E. coli pathogroup in fresh seafood. TP broth with SMAC agar performed better in yielding pathogenic E. coli from seafood. Pathogroup identification is necessary to assess pathogenic potentials of E. coli.